2020
DOI: 10.1021/acs.molpharmaceut.0c00559
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Differential Tissue Abundance of Major Non-CYP Enzymes in Human

Abstract: The availability of assays that predict the contribution of cytochrome P450 (CYP) metabolism allows for the design of new chemical entities (NCEs) with minimal oxidative metabolism. These NCEs are often substrates of non-CYP drugmetabolizing enzymes (DMEs), such as UDP-glucuronosyltransferases (UGTs), sulfotransferases (SULTs), carboxylesterases (CESs), and aldehyde oxidase (AO). Nearly 30% of clinically approved drugs are metabolized by non-CYP enzymes. However, knowledge about the differential hepatic versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 67 publications
5
63
1
Order By: Relevance
“…Thus, using the AOX modulated activity model, estimates of active AOX enzyme abundance in each tissue's S9 fraction were obtained. It was found that the active AOX abundance in the liver (21 pmol/mg S9 protein) is in general agreement with measured liver AOX abundance (11.96+/-4.46 pmol/mg S9 protein) described by Basit and colleagues (Basit et al, 2020). In addition, the published extra-hepatic AOX abundance levels for the heart and intestine were below the limit of quantification, which agrees with much lower estimated active AOX levels that we obtained using AOX activity (Table 2).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, using the AOX modulated activity model, estimates of active AOX enzyme abundance in each tissue's S9 fraction were obtained. It was found that the active AOX abundance in the liver (21 pmol/mg S9 protein) is in general agreement with measured liver AOX abundance (11.96+/-4.46 pmol/mg S9 protein) described by Basit and colleagues (Basit et al, 2020). In addition, the published extra-hepatic AOX abundance levels for the heart and intestine were below the limit of quantification, which agrees with much lower estimated active AOX levels that we obtained using AOX activity (Table 2).…”
Section: Resultssupporting
confidence: 88%
“…This model was able to accurately capture (adj. R 2 = 0.99) 4-oxo-carbazeran formation time-course data in all tissue S9 incubations (Figure 3), with estimated parameter values captured in The tissue fractions tested were chosen due to the identified expression levels of AOX in the tissue (Basit et al, 2020), the volume of tissue of the organ (Davies and Morris, 1993), and/or the lack of blood flow restriction pertaining to the tissue. While it would have been desirable to study additional human tissues beyond the scope of this work, it is unlikely, based on these criteria that any would contribute significantly to whole-body AOX clearance.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first study that investigated the quantitative effect of the interplay of host enzymes, transporters, and the gut microbiome on irinotecan tissuespecific disposition. Irinotecan hydrolysis to SN-38 was significantly higher in the intestine as compared to the liver (Figure 1), which corroborates with the higher intestinal abundance of CES2, the primary hydrolytic enzyme involved in SN-38 formation (Basit et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
“…enzyme was similar to that of its native counterpart in vivo. 24 Summation of the individual enzyme contributions in a specific tissue was then used to estimate the total metabolic activity in that tissue ( eq 4 ). The calculation process was exemplified by sofosbuvir hydrolysis rate prediction as shown in Supplementary Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“… 21 − 23 A recent proteomics study quantified various noncytochrome P450 (CYP) drug-metabolizing enzymes (DMEs) in assorted human tissues. 24 The expression patterns of many non-CYP DMEs differed markedly between organs, indicating tissue-dependent metabolism of non-CYP substrate drugs. However, prodrug-activating enzymes, such as serine hydrolases, have not been fully characterized in the human tissues most relevant to SARS-CoV-2 infection.…”
mentioning
confidence: 99%